Evolution of cancer suppression as revealed by mammalian comparative genomics. (February 2017) - Tollis, Marc; Schiffman, Joshua D; Boddy, Amy M
Abstract : Cancer suppression is an important feature in the evolution of large and long-lived animals. While some tumor suppression pathways are conserved among all multicellular organisms, others mechanisms of cancer resistance are uniquely lineage specific. Comparative genomics has become a powerful tool to discover these unique and shared molecular adaptations in respect to cancer suppression. These findings may one day be translated to human patients through evolutionary medicine. Here, we will review theory and methods of comparative cancer genomics and highlight major findings of cancer suppression across mammals. Our current knowledge of cancer genomics suggests that more efficient DNA repair and higher sensitivity to DNA damage may be the key to tumor suppression in large or long-lived mammals.